PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA DAN BERIMPLIKASI PADA KINERJA KARYAWAN Studi (Devisi Home Service) Pada PT. Telkom Indonesia Tbk Wilayah Jakarta Timur - Yoppy Mulyati Virginia dan Cicih Ratnasih (Fakultas Ekonomi Universitas Borobudur, 2017)
This study aims to determine the extent to which the influence of Working Environment And Job Stress on Work Productivity Has Implications On Employee Performance PT. Telkom Indonesia Tbk East Jakarta Region. The data used in this study in the form of primary data collected from respondents' answers based on questionnaires given, ie as many as 30 people. Data processing method using path analysis method (Path Analysis) with the help of SPSS version 22.0. The statistical test used the significance test of individual parameters (t test) and simultaneous significance test (Test F). The results showed that simultaneously the work environment variables, job stress and work productivity have a significant effect on employee performance. Partially shows that the analysis of 1: work environment variables significantly affect employee performance, while analysis 2: work stress variable significantly influence employee performance and on analysis 3: work productivity variables significantly affect employee performance. Keywords : Work Environment, Job Stress, Work Productivity, Employee Performance